Overcoming the Passivity Bounds in Communications Systems with Spacetime Modulations. - Moreno-Rodríguez, Salvador; Alex-Amor, Antonio; Pérez-Escribano, Mario; Valenzuela-Valdés, Juan Francisco; Padilla, Pablo; Molero, Carlos (My University, 2025)
In this paper, we exploit the extra degrees of freedom associated with including time as a design variable to create communication scenarios beyond the physical bounds of passive structures. We particularize the results to a time-modulated diffractive one-dimensional grating. By tuning the temporal modulation, we show that two different scenarios can lead to the same output angles but with different output frequencies or incidence angles. These results illustrate the potential of these metastructures as diffractive beamformers and frequency mixers.
Keywords: Electromagnetismo; Espacio y tiempo; Beamforming; Electromagnetics; Frequency conversion; Metamaterials; Spacetime modulation